1011 The Implications of The Use of Left Ventricular Assist Devices (Lvads) Or Extra-Corporeal Membrane Oxygenation (ECMO) In Patients with Severe Heart Failure. (12th October 2021) - Kumar, A
Abstract: Introduction: Heart failure (HF) is a chronic, debilitating and progressive disease(1). Consequently, guidelines recommend heart transplants for patients suffering from end-stage HF, termed destination therapy(2). However, with increasing disparity between the number of donor hearts available and people on the waiting list, identifying the most suitable interim intervention (bridge-to-transplant) therapy is paramount(3, 4). Method: A scoping search identified controversy surrounding LVAD versus ECMO in end-stage HF. Discussions with an expert in the field at a tertiary centre in the UK (Queen Elizabeth Hospital Birmingham) enabled refinement of the topic. A literature review was conducted, followed by a title and abstract screen. Subsequently, remaining literature was critically appraised. Results: First generation LVADs may decrease mortality by 48% in comparison to optimal medical management, although have been associated with disabling stroke. Second and third generation LVADs demonstrate impressive survival at 30 days (>95%), a strong favourable long-term prognostic indicator. Additionally, improvement in HF severity and QoL have been demonstrated. Unlike ECMO, LVAD appears to be feasible as a DT, lasting as long as 8 years. However, the cost of LVADs may be prohibitive, higher than transplantation2. However, ECMO may facilitate multi-organ and right ventricular recovery, enabling transplantation to occur with increased stability. Neither option has conclusive evidence for cost-effectiveness. Conclusions: Both LVADs and ECMO can be considered as effective BTT options, suitable in different clinical scenarios. The decision for BTT intervention should be undertaken on a case-by-case basis, in accordance with NICE guidelines, aiming for optimal outcomes in terms of survival, functionality and QoL.